Working Memory Beats Age: Evidence of the Influence of Working Memory on the Production of Children’s Emotional False Memories - Mirandola, Chiara; Pazzaglia, Francesca (Frontiers in Psychology, 2021)
Emotional valence and working memory ability (WM) affect false memories’ production in adults. Whereas a number of studies have investigated the role of emotional valence in children’s tendency to produce spontaneous false memories, individual differences in WM have not been previously included. In the current article, we were interested in investigating whether emotion and WM would interact in influencing the propensity to incur inferential false memories for scripted events. Ninety-eight typically developing children (first-, third-, and eighth- graders) were administered the Emotional false memory paradigm – allowing to study false memories for negative, positive, and neutral events – and a WM task. Results showed that regardless of age, valence influenced false memories’ production, such that positive events protected against incurring distortions. Furthermore, WM interacted with valence, such that children with higher WM abilities produced fewer false memories for negative events. Concerning confidence judgments, only the youngest group of children claimed to be overconfident when committing false memories for negative and neutral events. Results are discussed in terms of the role of individual differences in higher cognitive abilities interacting with the emotional content of to-be-remembered events.